Education in Tokugawa Japan - Dore, R. P. (The Athlone Press, 1965)
Japanese cultural life had reached a low ebb at the beginning of the Tokugawa period. The Japanese society which emerged when Tokugawa Ieyasu had completed the process of pacifying warring baronies was neither literary, nor hardly literate. The rulers were warriors and the people they ruled were largely illiterate. The Japan of 1868 was a very different society: practically every samurai was literate and it was a world in which books abounded. The transformation which had occurred in these two and a half centuries was an essential precondition for the success of the policy which the leaders of the Meiji Restoration were to adopt. An in-depth survey of the development and education during the period, this book remains one of the key analyses of the effects of Tokugawa educators and education on modern day Japan.